Soil nematode community responses to prescribed burning in upland moorland: temporal dynamics prevail over fire effects - Neilson, Roy; King, Dale; Hooper, Russell; Fielding, Debbie A.; Giles, Madeline E. (Frontiers in Soil Science, 2025)
Muirburn is a land management practice of upland Calluna vulgaris-dominated moorland landscapes that uses prescribed burning to maintain vegetation diversity, enhance the nutritional value of vegetation for livestock, and support game management. While the impacts of Muirburn are well characterized for aboveground diversity, there is a lack of equivalent data on the impacts of Muirburn on soil biodiversity. To address this, the impact of Muirburn on soil nematode communities was assessed over a 12-month period. Muirburn had no effect on soil nematode abundance, community structure, species richness, or functional group composition. However, irrespective of fire, there were temporal effects on nematode community structure likely driven by five genera representing several nematode functional groups: Bitylenchus, Filenchus, Plectus, Mesorhabditis, and Thonus. Nematode species richness also exhibited a temporal effect, although arguably this could have been driven by the final sampling time point. The relative composition of nematode functional groups also varied temporally. Results from this study contribute to addressing the significant knowledge deficit regarding the impacts of Muirburn practices on soil biodiversity and help to inform future best practice guidance for the prescribed burning of upland moorland.